4 Quality of life assessment in palliative care day services. Issue 3 (1st September 2017) - Armstrong, Mary; Dempster, Martin; Donnelly, Michael; McCorry, Noleen; Graham, Lisa
Abstract : Introduction: The outcome measure used to assess Quality of Life (QoL) can have a crucial effect on the interpretation of any findings in palliative care. Aims: To compare the sensitivity to change of the Schedule for the Evaluation of Individual Quality of Life-Direct Weighing (SEIQol-DW), the McGill Quality of Life Questionnaire (MQOL) and the Short Form 36 (SF-36) among patients receiving Palliative Care Day Services (PCDS). Methods: Patients were recruited from PCDS. The same questionnaires were administered at 2 time points, approximately 3 weeks apart. A measure of dependency (the Barthel Index) was used to determine whether patients remain stable/deteriorate over time. Analysis: Standardised response mean (SRM) was used to determine the relative sensitivity of each instrument for those patients who had changed in their Barthel scores (Garratt et al 1994). Results: Forty four patients (median 69 years, range 49–86) were recruited. Follow-up data was obtained from 25 (56.8%) patients. Of these 25 patients, 14 (56%) patients changed according to the Barthel Index with 7 (50%) patients defined as increased dependency. The responsiveness of the SEIQoL-DW was larger than those of the other questionnaires (SRM=0.73) for those patients who showed an increased dependency over time. The SF-36 Bodily Pain subscale demonstrated a larger responsiveness than the other questionnaires (SRM=0.82) for those patients who showed a decrease dependency over time. Conclusions: The SEIQoL appears to be a good outcome measure for charting the progress of patients who are deteriorating over time. However none of the questionnaires were particularly good at demonstrating improvements over time. Reference: 1. Garratt AM, Ruta DA, Abdalla MI, Russell IT. SF-36 health survey questionnaire: II. Responsiveness to changes in health status in four common clinical conditions. Quality in Health Care1994;3:186–192.